2006
DOI: 10.1249/01.mss.0000218130.41133.cc
|View full text |Cite
|
Sign up to set email alerts
|

The Congenital Long QT Syndrome and Implications for Young Athletes

Abstract: The congenital long QT syndrome (LQTS) is caused by cardiac ion channel mutations, which predispose young individuals to sudden cardiac death often related to exercise. The issue of LQTS and sports participation has received significant publicity due to reports of sudden death in young competitive athletes. This article reviews the pathophysiology, clinical characteristics, and management of LQTS in the physically active and athletic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…The various types of congenital long QT syndromes have an estimated prevalence of 1:5,000 in the general population. Studies on competitive athletes indicated similar prevalence [4,25]. Approximately 10% of patients with long QT syndrome die due to sudden cardiac death.…”
Section: Genetic Defectsmentioning
confidence: 95%
“…The various types of congenital long QT syndromes have an estimated prevalence of 1:5,000 in the general population. Studies on competitive athletes indicated similar prevalence [4,25]. Approximately 10% of patients with long QT syndrome die due to sudden cardiac death.…”
Section: Genetic Defectsmentioning
confidence: 95%
“…[26][27][28][29][30] In health, adequate coronary blood flow reserve and normal cardiac electrical activity occur during vigorous exercise. However, in the presence of coronary artery disease, the production of malignant substrates during or immediately after exercise stress might trigger a cascade of physiological events precipitating an adverse event (Fig.…”
Section: Pathophysiology Of Exercise-induced Adverse CV Eventsmentioning
confidence: 99%
“…Exercise testing may enhance diagnostic accuracy because shortening of the QT interval during effort is inadequate and/or repolarisation abnormalities become more prominent and recognisable after exercise (in the recovery phase) in patients with LQTS. The ECG response to exercise may vary according to LQTS genotype: the QTc prolongs in LQT1, remains unchanged in LQT2, and shortens excessively in LQT3 patients 69. Athletes with a clear-cut prolonged QTc interval should be referred to a cardiac specialist for definitive diagnosis and risk stratification of LQTS, including molecular screening of causative gene mutations.…”
Section: Uncommon and Training-unrelated Ecg Changesmentioning
confidence: 99%